PENGEMBANGAN VIDEO PEMBELAJARAN MATEMATIKA BERBANTUAN VEGAS PRO 13 UNTUK MENINGKATKAN PRESTASI BELAJAR SPLTV SISWA MADRASAH ALIYAH - Saifullah Saifullah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to (1) describe the process of developing learning video media (2) describe the feasibility of video-based learning media, and (3) describe the improvement of student learning achievement outcomes with learning video media on the subject matter of SPLTV. The type of research used is development research (R&D) with the ADDIE development model and one group pretest postest research design that produces products in the form of learning video media. The technique of data collection in this study used questionnaires, pre-test and post-test results, and interviews. The resulting data are analyzed quantitatively and descriptively qualitatively.The results of this study are, (1) the product development process that has been generated from this research and development is obtained through several processes, namely product manufacturing, product validation, revision, and field trials, (2) the feasibility of learning video media media can be seen from the validity of media experts 84.71% and material experts 78.33%, 71.54% practicality from practitioners / teachers, 83.03% effectiveness of product trials and 80% of the ministry of field trials, thus the learning video media including valid, feasible, practical, effective and interesting categories used, (3) student learning achievement results increased as evidenced by pre-test results that originally got a result of 50.97 then in post-test results increased to 60.28.